1996
DOI: 10.1097/00003246-199606000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Breathing measurement reduces false-negative classification of tachypneic preextubation trial failures

Abstract: Tachypnea as a marker of respiratory distress is sensitive, but is not sufficiently specific to be used as a criterion in preextubation trials. Reliance on tachypnea as a preextubation trial failure criterion is likely to prolong intubation and ventilatory support for a large number of patients. Patient risks, determined by the extubation failures and reintubation rate, are the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…Indeed, it is conceivable that iatrogenic factors such as endotracheal tube discomfort or demandvalve insensitivity/unresponsiveness, rather than true ventilator dependence, caused the failure of the SBT in at least some of these patients. 3,15,[32][33][34][35] Thus, it is unclear how many patients who are unable to tolerate an SBT would still be able to tolerate long-term ventilator discontinuation. Although the number is likely to be small, it is probably not zero, and this needs to be considered when dealing with patients who repeatedly fail an SBT.…”
Section: The Evidence Base Supporting Ventilator Withdrawal Strategiementioning
confidence: 99%
“…Indeed, it is conceivable that iatrogenic factors such as endotracheal tube discomfort or demandvalve insensitivity/unresponsiveness, rather than true ventilator dependence, caused the failure of the SBT in at least some of these patients. 3,15,[32][33][34][35] Thus, it is unclear how many patients who are unable to tolerate an SBT would still be able to tolerate long-term ventilator discontinuation. Although the number is likely to be small, it is probably not zero, and this needs to be considered when dealing with patients who repeatedly fail an SBT.…”
Section: The Evidence Base Supporting Ventilator Withdrawal Strategiementioning
confidence: 99%
“…We therefore conclude that compliance with the spontaneous breathing trial is one critical feature characterizing our patient collective. Based on previous findings reporting that 105 out of 589 extubated patients had a preextubation respiratory rate >30 breaths/ min [41] , one might suppose that spontaneous breathing would have principally been possible in some of our patients. However, due to obvious vegetative stress and the patients' impaired insight into the actual clinical condition, such a procedure seems questionable in stroke patients.…”
Section: Discussionmentioning
confidence: 85%
“…Many investigators have demonstrated reliable predictors of successful extubation or discontinuation of MVS [2], and among them, the ratio of respiratory frequency to tidal volume (f/V T ) [3, 4, 5, 6, 7, 8], the work of breathing [9, 10, 11]and the oxygen cost of breathing (OCOB) [12, 13, 14, 15]have frequently been found to be the most reliable. However, these results have aroused controversy at present.…”
Section: Introductionmentioning
confidence: 99%